The Blockchain Technology Applications and its Impact on Governance Performance: A Field Study on the Transportation Sector in Palestine - Abu Farhah, Maher Fuad (Journal of engineering sciences and information technology, 2024)
Objectives: Blockchain technology (BCT) is an advance technical solution incorporating many technologies, with the capacity to overcome governance’s limitations. As a consequence, our study aims to analyzing how BCT applications affect governance performance (GP), testing the mediating role of operational efficiency (OE) in the ministry of transport in Palestine (MTP). This study was conducted during the period from 2022 to 2024. Methods: A paper applied research design (Survey), and a study unit consisting of 90 participants at MTP was used out of the target population (110). In contrast, simple random and stratified sampling techniques were applied for the determination of the research sample. Data collected via questionnaires and the study’s hypotheses were evaluated using PLS-SEM. Results:. The main results showed that BCT and their impact on GP from the perspective of employees were high. Until the period of the research, Palestine lacked a clear strategy and policy for the usage of BCT. There was an impact of BCT dimensions on GP at the level of significance. OE has a fully mediating role in the effect of decentralization & traceability and a partial mediating role in the effect of transparency on GP. Conclusions: The paper advises MTP management to start a sound BCT and invest in it concurrently in order to materialize OE and achieve GP efficiency. Future studies can apply the study model to other sectors to verify the reliability of the model.